The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7717/peerj.9483
|View full text |Cite
|
Sign up to set email alerts
|

Plastome comparative genomics in maples resolves the infrageneric backbone relationships

Abstract: Maples (Acer) are among the most diverse and ecologically important tree genera of the north-temperate forests. They include species highly valued as ornamentals and as a source of timber and sugar products. Previous phylogenetic studies employing plastid markers have not provided sufficient resolution, particularly at deeper nodes, leaving the backbone of the maple plastid tree essentially unresolved. We provide the plastid genome sequences of 16 species of maples spanning the sectional diversity of the genus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 98 publications
7
13
0
Order By: Relevance
“…Most nodes of the reconstructed phylogenomic tree had 100% bootstrap support values, indicating a suitable evolutionary placement for Acer species (Figure 4). The results showed that Acer and Dipteronia are monophyly, which is consistent with previous studies (Renner et al, 2008;Gao et al, 2020;Wang et al, 2020;Areces-Berazain et al, 2021). Acer pictum subsp.…”
Section: Phylogenetic Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…Most nodes of the reconstructed phylogenomic tree had 100% bootstrap support values, indicating a suitable evolutionary placement for Acer species (Figure 4). The results showed that Acer and Dipteronia are monophyly, which is consistent with previous studies (Renner et al, 2008;Gao et al, 2020;Wang et al, 2020;Areces-Berazain et al, 2021). Acer pictum subsp.…”
Section: Phylogenetic Analysissupporting
confidence: 92%
“…Although many studies have placed A. sino-oblongum in Section Palmata (van Gelderen et al, 1994;Xu et al, 2008), the taxonomic status of this species must be revisited. Acer yangbiense, a rare and critically endangered species, is herein shown to be genetically distant from the other species in Section Lithocarpa, as in previous studies Areces-Berazain et al, 2021). This species has pale white to pale gray leaf blade abaxially, entire leaf margin, and slender fruiting pedicels, which are pretty different from other species in the Section Lithocarpa (van Gelderen et al, 1994;Xu et al, 2008).…”
Section: Phylogenetic Analysissupporting
confidence: 65%
See 2 more Smart Citations
“…We used ModelTest-NG v0.1.5 ( Darriba et al 2019 ) to select the best-fitting nucleotide substitution model for the plastome dataset [with one inverted repeat (IR) removed]. No partition was defined because, in our experience with plastome data, we have not observed an effect of partitioning on tree inference (see Areces-Berazain et al 2020 ). A maximum likelihood (ML) tree was built with RAxML-NG v0.9.0 ( Kozlov et al 2019 ) using the GTR+I + G model.…”
Section: Methodsmentioning
confidence: 99%